KEMAMPUAN SELF DIRECTED LEARNING DAN PENCAPAIAN HASIL BELAJAR: Studi Cross Sectional - Isnaini, muhamad; Adi Putra, Andi Budiyanto; Sartika, Fanny Dewi; Arifuddin, Fitrawati (Universitas Islam Negeri Alauddin Makassar, 2019)
The ability of professional nurses to be independent in their learning process is one way to ensure continued improvement and mastery of advance competencies in professional nursing practice. Efforts are being made to improve the ability of SDL is expected to encourage the achievement of nursing competency standards, which are responsible for lifelong learning, professional development and maintain their competence. The aims of this study are to determine the students’ SDL ability during clinical education after being involved in PBL curricula, to analyze the relationship between SDL ability and students’ learning outcomes during clinical practice and to explain the description of students’ SDL process. The design of quantitative was cross sectional approach and data collection using SDLRS Fisher questionnaire. Qualitative used in-depth. The participants were 60 students of Akper Syekh Yusuf Gowa who involved in the clinical education. The average score of student’s self-directed learning ability was 154. The Pearson correlation test showed a positive relationship between the ability of SDL and the achievement of learning outcomes(r= 0.373 and p<0.05). Results of the qualitative data analysis showed who had high SDL score were able to perform all SDL according Knowles SDL process description. Students with high score have already internalizing SDL values. Students with low score only able to perform half of SDL process which was stated by Knowles (1975), students have not internalizing SDL values yet.